2011
DOI: 10.1007/s00277-011-1231-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated frequencies of leukemic myeloid and plasmacytoid dendritic cells in acute myeloid leukemia with the FLT3 internal tandem duplication

Abstract: Some 30% of acute myeloid leukemia (AML) patients display an internal tandem duplication (ITD) mutation in the FMS-like tyrosine kinase 3 (FLT3) gene. FLT3-ITDs are known to drive hematopoietic stem cells towards FLT3 ligand independent growth, but the effects on dendritic cell (DC) differentiation during leukemogenesis are not clear. We compared the frequency of cells with immunophenotype of myeloid DC (mDC: Lin−, HLA-DR+, CD11c+, CD86+) and plasmacytoid DC (pDC: Lin−, HLA-DR+, CD123+, CD86+) in diagnostic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 25 publications
2
39
2
Order By: Relevance
“…These leukemic DCs contained ITD mutations and could be driven to differentiate into mature mDCs or pDCs in vitro upon culture with cytokines, but they were not fully capable of secreting several cytokines [14]. We therefore deduced that CD11c + , CD123 + , and CD11c + /CD123 + leukemic DCs were arrested in the dendritic cell differentiation pathway and that CD11c + and CD123 + should be rather considered as DC precursor markers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These leukemic DCs contained ITD mutations and could be driven to differentiate into mature mDCs or pDCs in vitro upon culture with cytokines, but they were not fully capable of secreting several cytokines [14]. We therefore deduced that CD11c + , CD123 + , and CD11c + /CD123 + leukemic DCs were arrested in the dendritic cell differentiation pathway and that CD11c + and CD123 + should be rather considered as DC precursor markers.…”
Section: Resultsmentioning
confidence: 99%
“…Incomplete regeneration of DC populations in leukemia patients after stem cell transplantation has also been described in the literature as a negative prognostic factor [25, 26]. We have previously demonstrated that the presence of the ITD mutation in AML was correlated with an aberrant accumulation of cells with hallmarks of arrested dendritic cells [14]. We hypothesized that constitutive signaling through FLT3-ITD could arrest MRD leukemic dendritic cell precursors in an immature stage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…47 Recent studies revealed that APCs such as pDCs play a tumor-promoting role in MM patients 48 and potentially also in AML patients. 49 CpG(A)-STAT3 siRNA provides a new method for targeting abnormal human DC populations in the tumor microenvironment to restore antitumor immunity while reducing survival of TLR9 ϩ tumor cells. Our proof-of-principle studies combining CpG-Stat3 siRNA with local radiotherapy have demonstrated that targeting both tumor and the tumor microenvironment is effective against radiation-resistant mouse BCL.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are at very high risk of leukemia recurrence, and therefore the standard of care commonly includes hematopoietic stem cell transplantation (HSCT) and adoptive T-cell transfer (Schlenk et al, 2008;Bacher et al, 2009). Studies from our group with diagnostic and remission samples obtained from FLT3-ITD patients showed a deregulated dendropoiesis, accumulation of dendritic cell precursors, and aberrant expression of inflammatory cytokines (Rickmann et al, 2011). Notably, FLT3-ITD occurrence has been correlated with WT1 overexpression (Spassov et al, 2011).…”
mentioning
confidence: 96%